Broad‐ and small‐scale environmental gradients drive variation in chemical, but not morphological, leaf traits of vascular epiphytes. (6th June 2022) - Guzmán‐Jacob, Valeria; Guerrero‐Ramírez, Nathaly R.; Craven, Dylan; Brant Paterno, Gustavo; Taylor, Amanda; Krömer, Thorsten; Wanek, Wolfgang; Zotz, Gerhard; Kreft, Holger
Abstract: Variation in leaf functional traits along environmental gradients can reveal how vascular epiphytes respond to broad‐ and small‐scale environmental gradients. Along elevational gradients, both temperature and precipitation likely play an important role as drivers of leaf trait variation, but these traits may also respond to small‐scale changes in light, temperature and humidity along the vertical environmental gradient within forest canopies. However, the relative importance of broad‐ and small‐scale environmental gradients as drivers of variation in leaf functional traits of vascular epiphytes is poorly understood. Here, we examined variation in morphological and chemical leaf traits of 102 vascular epiphyte species spanning two environmental gradients along Cofre de Perote mountain in Mexico: (i) a broad‐scale environmental gradient approximated by elevation as well as by species' lower and upper elevational limits, and (ii) small‐scale environmental gradients using the relative height of attachment of an epiphyte on a host tree as a proxy for variation in environmental conditions within the forest canopy. We also assessed whether variation in morphological and chemical leaf traits along these gradients was consistent across photosynthetic pathways (CAM and C3 ). Broad‐ and small‐scale environmental gradients explained more variation in chemical traits (marginal R 2 : 11%–89%) than in morphological traits (marginal R 2 : 2%–31%). For example, leaf carbon isotope signatures (δ 13 C), which reflects water‐use efficiency, varied systematically across both environmental gradients, suggesting a decrease in water‐use efficiency with increasing lower and upper elevational limits and an increase in water‐use efficiency with relative height of attachment. The influence of lower and upper elevational limits on trait variation differed between photosynthetic pathways, except for leaf dry matter content and leaf nitrogen‐to‐phosphorus ratio. Contrary to our expectations, broad‐ and small‐scale environmental gradients explained minimal variation in morphological leaf traits, suggesting that environmental conditions do not constrain morphological leaf trait values of vascular epiphytes. Our findings suggest that assessing multiple drivers of leaf trait variation among photosynthetic pathways is key for disentangling the mechanisms underlying responses of vascular epiphytes to environmental conditions. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: La variación de los rasgos funcionales de las hojas a lo largo de los gradientes ambientales puede revelar cómo las epífitas vasculares responden a cambios ambientales a escalas grandes y pequeñas. A lo largo de gradientes altitudinales, probablemente, temperatura y precipitación desempeñan un papel importante detrás de la variación de los rasgos foliares, pero estos rasgos también pueden responder a cambios ambientales a pequeña escala, por ejemplo, la variación en luz, temperatura y humedad a lo largo de un gradiente ambiental vertical dentro del dosel del bosque. Sin embargo, la importancia relativa de los gradientes ambientales a gran y pequeña escala como impulsores de la variación de rasgos funcionales de las hojas en epífitas vasculares es poco conocida. Aquí, examinamos la variación en los rasgos morfológicos y químicos de hojas de 102 especies de epífitas vasculares, abarcando dos gradientes ambientales a lo largo de la montaña del Cofre de Perote en México: i) un gradiente ambiental a gran escala reflejado en cambios de elevación, así como variación en los límites de elevación inferior y superior de las especies, y ii) gradientes ambientales a pequeña escala, reflejado en la altura relativa de fijación de una epífita en un árbol huésped, indicando la variación en las condiciones ambientales dentro del dosel del bosque. También evaluamos si la variación en los rasgos morfológicos y químicos de las hojas a lo largo de estos gradientes es consistente entre vías fotosintéticas (CAM y C3 ). Los gradientes ambientales explicaron mayor variación en los rasgos químicos (R2 marginal: 11‐89%) que en los rasgos morfológicos (R2 marginal: 2‐31%). Por ejemplo, las firmas isotópicas de carbono de las hojas (δ13C), que reflejan la eficiencia en el uso del agua, variaron sistemáticamente a través de ambos gradientes ambientales, sugiriendo una disminución de la eficiencia en el uso del agua con el aumento de los límites de elevación inferior y superior y un aumento de la eficiencia en el uso del agua con la altura relativa de fijación. La influencia de los límites de elevación inferior y superior en la variación de los rasgos difirió entre las vías fotosintéticas, excepto para el contenido de materia seca de hojas y la relación nitrógeno‐fósforo. Al contrario de lo que esperábamos, los gradientes ambientales a gran y pequeña escala explicaron una variación mínima en los rasgos morfológicos de las hojas, lo que sugiere que las condiciones ambientales no limitan la variación en los rasgos morfológicos de las hojas de las epífitas vasculares. Nuestros resultados sugieren que la inclusión de múltiples impulsores explicando la variación de los rasgos foliares entre vías fotosintéticas es clave para desentrañar los mecanismos detrás de las respuestas de las epífitas vasculares a las condiciones ambientales.